PEMERIKSAAN PROTHROMBIN TIME DAN ACTIVATED PARTIAL THROMBOPLASTIN TIME DENGAN HUMACLOT VA SERTA SYSMEX CA 500 - Misnah Misnah; Agus Alim Abdullah; Mansyur Arif; Burhanuddin Bahar (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
Prothrombin Time (PT) and an activated Partial Thromboplastin Time (aPTT) are routine coagulation tests used for pre-operative screening. The analytical step as one of the laboratory test’s stage that plays the role in the determination of the test is influenced by several factors, one of them is choosing its proper devices. The aim of this study was to know the correlation of the PT and aPTT test’s result using Humaclot VA and Sysmex CA 500 devices. A cross sectional study has been done at the Clinical Pathology Laboratory of Wahidin Sudirohusodo Hospital Makassar started from May 2009 until June 2009. The data were analyzed with T and Pearson’s Correlation test. From the 50 samples were obtained the percentage of the corresponding frequency of the PT results between Humaclot VA and Sysmex CA 500 about 84%, whereas the frequency of the corresponding results aPPT between Humaclot VA and Sysmex CA 500 is 76%, the Pearson correlation test for PT=0.58, and aPTT=0.38. There were found the suitability of PT, aPTT of Humaclot VA with CA 500 and both tools have a positive correlation.